AI-driven Quantum Dot Transistors for Ultra-Low Power Computing - Mishra, Archana; Kadao, Anjali Krushna; Rohilla, Shruti (International Journal of Engineering, Science and Information Technology, 2025)
Since Quantum Dot Transistors (QDTs) provide a transformative approach to ultra-low power computing, yet their optimization is an open problem, a proposed paradigm shift in computing is used as an example application context for creating new processors. The framework of this research is an AI-based approach to dynamically improve the QDT's efficiency and flexibility using reinforcement learning and neuromorphic AI. The intelligent tuning mechanism proposed uses a sample-as-a-service approach to optimize charge transport and lower leakage currents, as well as minimize energy dissipation according to real-time workload. To precisely control and self-adjust from transistor behavior to a varying environmental condition, it integrates a hybrid quantum-classical AI model. Furthermore, the mechanism adopts self-healing features to autonomously reconfigure transistor networks when anomalies are encountered, ensuring fault tolerance and extending device longevity. Simulations are used to validate the proposed methodology, which is shown to improve power efficiency, switching speed, and operational stability a great deal versus conventional low-power transistors. This work takes most of the power of QDTs for next-generation energy-efficient electronics such as IoE, edge computing, and neuromorphic processors by leveraging AI-driven optimization. Their findings provide significant contributions in the emerging field of AI-assisted semiconductor technology toward developing a scalable and intelligent method for designing ultra-low power devices. Future advancements in sustainable computing lie in the performance improvements while decreasing the digital system’s environmental footprint that this research enables.